320 mm InterTan nail optimizes biomechanics in AO/OTA 31A2.3 fractures: superior stress distribution, micromotion, and strain for enhanced healing - Wang, Pao; Gu, Shengjie; Liu, Zhiwei; Li, Ning; Lan, Chengsong; Zhang, Biao; Liu, Gang (Frontiers in Bioengineering and Biotechnology, 2026)
PurposeThis study compares the biomechanical performance of InterTan nails of three lengths (180 mm, 240 mm, and 320 mm) in treating AO/OTA 31A2.3 comminuted intertrochanteric fractures, which are highly unstable and prone to fixation failure. The research question focuses on identifying the nail length that optimizes stress distribution, displacement, and strain to enhance fracture healing and reduce failure risk, thereby providing a theoretical foundation for clinical decision-making.MethodsFemoral CT images from a healthy 24-year-old male were used to reconstruct cortical and cancellous bone models in Mimics Research 21.0 and Geomagic Wrap 2021. A complete femur and AO/OTA 31A2.3 fracture model were constructed in SolidWorks 2022. InterTan models (180 mm, 240 mm, and 320 mm) were assembled with the fracture model, and finite element analysis (FEA) was performed in Ansys Workbench 18.0 under three loading conditions (standing, walking, and stair descent) to evaluate stress, deformation, and failure risk.ResultsStress concentrated at the nail-screw junction and proximal aperture, with the 180 mm nail exhibiting the highest stress, the 320 mm nail the lowest, and the 240 mm nail intermediate values. Displacement increased with nail length under dynamic loads, whereas the 180 mm nail minimized displacement during standing. The 240 mm nail showed the lowest strain during standing but the highest during stair descent. Differences in stress and displacement were statistically significant (P < 0.05).ConclusionThe 320 mm nail optimizes stress distribution, micromotion, and strain, thereby reducing failure risk and promoting healing. These findings align with biological osteosynthesis principles and support personalized treatment strategies.